The Impact of e-Song and Language Games on Kadazandusun Pupils’ Vocabulary Mastery - Minah Sintian; Viannie Tongguritom; Jesseca Dunis; Ainah Gimir; Nur Qistina Abdul Razak (Journal of Research in Education and Pedagogy, 2026)
Vocabulary knowledge is the foundation for mastering a language. The vocabulary mastery of primary school pupils in rural areas who learn the Kadazandusun language (BKD) as a second or third language can be significantly enhanced through well-planned learning strategies that yield positive pedagogical impacts. This study aims to evaluate the effectiveness of utilizing e-song media and language games to improve BKD vocabulary mastery among primary school pupils. Employing a quasi-experimental design, this study utilized pre- and post-tests to compare treatment and control groups. The teaching interventions were implemented with BKD pupils in schools located in the interior of Sabah. The e-song media was administered to a non-random sample of 30 Year Four pupils from two primary schools: SK Saint Pius Pamilaan, Tenom, and SK Senangang, Keningau. Meanwhile, the language games intervention involved an intact group sample of 20 Year Three pupils at SK Ulu Sapi, Telupid, divided into control and treatment groups based on existing class structures. The control groups were taught using conventional materials, whereas the treatment groups utilized e-songs and language games. Following the intervention, the e-song treatment group’s post-test scores increased significantly to a mean score of 80.07, compared with the control group’s mean score of 53.47. Similarly, the language games treatment group achieved a post-test mean score of 80, whereas its corresponding control group scored a mean of 29. These results indicate that both digital media and game-based methods significantly improve pupils’ vocabulary mastery. Ultimately, this study highlights the value of diversifying authentic learning strategies that can be adapted to various educational contexts, resources, and teacher-led initiatives.